Perpektif Islam pada Kinerja Pemasaran Dengan Orientasi Pasar UMKM di Kabupaten Lamongan - Hifi Rini Puspita; Savitri (FADZAT: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the influence of Islamic values-based market orientation and the integration of Islamic values ??into market orientation on the marketing performance of Micro, Small, and Medium Enterprises (MSMEs) in Lamongan Regency. The study employed a quantitative approach with an explanatory design. Data were collected through a structured questionnaire from 100 MSMEs selected using a purposive sampling technique. Data analysis was conducted using linear regression analysis to test the causal relationship between the research variables. The results showed that a market orientation based on Islamic values ??had a positive and significant effect on the marketing performance of MSMEs. The application of Sharia principles, such as honesty, fairness, trustworthiness, and responsibility in marketing activities, has been shown to increase consumer trust and loyalty, thus improving marketing performance. Furthermore, the integration of Islamic values ??into market orientation, reflected in product information transparency, adherence to halal and ?ayyib principles, and ethical business competition, has been shown to strengthen the competitiveness and sustainability of MSMEs. These findings confirm that Islamic values ??serve not only as normative guidelines but also have strategic implications for improving MSME marketing effectiveness. This research provides theoretical contributions in the development of market orientation studies from an Islamic economic perspective as well as practical implications for MSMEs and policy makers in formulating ethical, competitive, and sustainable marketing strategies.